Determinasi Gaya Kepemimpinan, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan PT Pos Indonesia Persero Jakarta Tahun 2026 - Parindra, Rhonie; Hadi, Nafik Umurul (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
Employee performance is a crucial pillar in maintaining service stability, efficiency, and operational productivity within public agencies and State-Owned Enterprises (BUMN). This study aims to analyze the positive and significant influence of Leadership Style, Work Discipline, and Work Motivation on Employee Performance at the Head Office of PT Pos Indonesia (Persero) Jakarta. The research adopts a quantitative approach utilizing multiple linear regression analysis methods. Data collection was conducted through the distribution of structured questionnaires to eighty-one employees at the Head Office of PT Pos Indonesia (Persero) Jakarta, selected via a purposive sampling technique. The partial statistical results through the t-test demonstrate that Leadership Style and Work Discipline both exert a positive and significant effect on Employee Performance. This indicates that an adaptive leadership style coupled with well-structured, humanistic regulations serves as a professional guideline that optimizes field execution. Concurrently, Work Motivation is proven to have a positive and highly significant effect, emerging as the most dominant variable driving daily productivity. Simultaneously through the F-test, all independent variables exhibit a substantial and highly significant impact on employee performance. The coefficient of determination value of ninety-nine point one percent indicates that these three variables play an exceptionally powerful role in explaining and predicting corporate operational outcomes. The concrete implication of this research suggests that the management of PT Pos Indonesia must continuously sustain intrinsic work motivation through performance incentives and support a collaborative leadership ecosystem to maintain high service delivery standards in the digital logistics era.